Penerapan Metode Random Forest untuk Prediksi Win Ratio Pemain Player Unknown Battleground - Haristu, Reinardus Aji; Rosa, Paulina H. Prima (MEANS (Media Informasi Analisa dan Sistem), 2019)
Online game that is on the rise as one of e-sports is the unknown battleground player. To win the game requires the right strategy. In this paper, a study of effective playing strategies in the player unknown battleground game is explored by extracting data from player statistics taken from the kaggle website. From the statistical data, a model is made to predict the win ratio of each player using the random forest method. From the results of the study, random forest was able to produce an accuracy of 88.19%.